Editorial - Levent Özçakar, (Archives of Rheumatology, 2014)
Dear Authors and Readers, We are very much pleased and honored to announce that the editorial team of our journal has recently changed. Similar to the former teams (to whom we are greatly indebted), together we will try our best to promote this journal. With this in mind, we have already started to revise and introduce several new features pertaining to the journal's name, website, style, author instructions, etc. First of all, we opted to change the name of our journal as Archives of Rheumatology. This way, we believe that the journal would be better recognized internationally. Being aware that convenient/prompt contact with the editorial team is paramount, we have provided personal correspondence to the journal's editorial secretary, editor-in-chief, and technical team. Herewith, aside from increasing the number of associate editors, a new position (i.e. editorial secretary) has been established for the Archives of Rheumatology. In addition, the early release of accepted papers, which will promote the concept of being author/reader-friendly, will be implemented as well. Accordingly, in a very short time period, not only will the readers have access to cutting-edge research, but they will also be able to get proofs and DOI numbers in advance of their publications. We strongly believe that education via scientific publishing is noteworthy. As such, we have started quarterly Let's Write a Manuscript (LWM) courses under the umbrella of TLAR and the Archives of Rheumatology. Furthermore, we will also be launching the smart phone application of our journal shortly. Of note, the new editorial members have also revised our application to PubMed Central and look forward to receiving a favorable response from them in the near future. Last but not least, we strongly hope that the Archives of Rheumatology will continue its journey toward ameliorating the lives of people with arthritis or other musculoskeletal problems. On behalf of the editorial team, Levent Özçakar, MD, Professor Editor-in-Chief